Using submaximal exercise heart rate for monitoring cardiorespiratory fitness changes in professional soccer players: a replication study - Altmann, S.; Neumann, R.; Härtel, S.; Woll, A.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To assess the value of monitoring changes in fitness in professional soccer players, using changes in heart rate at submaximal intensity (HR12km/h) over the velocity at a lactate concentration of 4 mmol/L (v4mmol/L). The authors reexamined (1) a range of threshold magnitudes, which may improve detecting substantial individual changes and (2) the agreement between changes in these 2 variables.